Liquefaction Analysis using Shear Wave Velocity - Filali Kamel; Sbartai Badreddine (Civil Engineering Journal, 2020)
The Andrus and Stokoe curves developed based on shear wave velocity case history databases, are the most widely used in the context of the Seed and Idriss simplified procedure as a deterministic model. Theses curves were developed from the database according to the calculate cyclic stress ratio (CSR) proposed by Seed and Idriss in 1971 with the assumption that the dynamic cyclic shear stress (τd) is always less than the simplified cyclic shear stress (τr) deduced by Seed and Idriss based on their simplifying hypotheses (rd= τd / τr <1). Filali and Sbartai in 2017, showed that rd can in many cases be greater than 1, and they have proposed a correction for the CSR in the range where rd >1. In this paper, we will present a probabilistic study based on the Bayesian method for the evaluation of the liquefaction potential of a soil deposit using a case history database based on shear wave velocity measurement. The result of this analysis shows that by using the corrected version of the simplified method, the boundary curve is moved to a new position. Then, the objective of this study is to present an adjusted mathematical model which characterizes the new position of the boundary curve (CRR) and a new formulation for computing the probability of liquefaction based on the probabilistic shape of the CRR curves using the corrected and the original version of the simplified method.